Attachment Patterns in Subjects Diagnosed With a Substance Use Disorder: A Comparison of Patients in Outpatient Treatment and Patients in Therapeutic Communities - Vismara, Laura; Presaghi, Fabio; Bocchia, Maria; Ricci, Rosolino Vico; Ammaniti, Massimo (Frontiers in Psychiatry, 2019)
The purpose of the present study is to analyze the quality of attachment in substance abuse patients in outpatient treatment vs. patients in therapeutic communities in order to identify the role of attachment insecurity in choosing a care system. The sample consisted of 127 subjects (107 males and 20 females); 97 were outpatients (83 males) and 30 therapeutic community patients (24 males). Attachment with respect to current, significant relationships was assessed using the Relationship Questionnaire. In the outpatient subgroup, the prevailing attachment style was preoccupied; for the therapeutic community patients, the prevailing attachment style was dismissive. The dimensions of care (how the caregiver is perceived as loving and caring) and overprotection (how the caregiver is perceived as intrusive and interfering)—evaluated by means of the Parent Bonding Instrument—were higher in the outpatient subgroup. Scores were higher with respect to maternal subscales regardless of treatment modality. No differences emerged with respect to self-perceived symptoms (SCL-90-R) between the subgroups; however, fearful-avoidant and dismissive-avoidant individuals reported higher self-perceived symptom regardless of treatment modality. Understanding the distribution of different attachment patterns with respect to the treatment modality may improve efficacious interventions, attuning them to the individual and his or her developmental environment.